Sorafenib maintenance after allogeneic stem cell transplantation in patients with FLT3+ AML receiving midostaurin during induction and consolidation: a retrospective analysis - Sapienza, Giuseppe; Castronovo, Marta; Tringali, Stefania; Bono, Roberto; Rotolo, Cristina; Mulè, Antonino; Calafiore, Valeria; Patti, Caterina; Agueli, Cecilia; Randazzo, Valentina; Santoro, Alessandra; Matranga, Domenica; et al. (Frontiers in Oncology, 2024)
IntroductionAcute myeloid leukemia (AML) relapse is the main cause of death after allogeneic stem cell transplant (allo-SCT). In AML FLT3+, it was shown that Sorafenib used as maintenance therapy after allo-SCT, significantly reduces the risk of relapse and death. MethodsWe analyzed 29 adult patients with FLT3m AML and underwent allogeneic stem cell transplant from 2019 to 2023. All patients received midostaurin plus conventional CT during induction and consolidation. After transplantation, Sorafenib maintenance was administered in all patients independently from MRD status at transplantation. ResultsSorafenib maintenance was applied in 18 patients out 29 patients (62%). Median time to start sorafenib was 100 days (range 37-225) and median duration of treatment was 775 days (range 140-1064). For the whole population (n=29), 2-year OS, LFS, and CIR was 76%, 68% and 28%, respectively. The median time to relapse was 137 days (range 49-246). For patients treated with sorafenib (n=18), the 2-year OS, LFS, and CIR were 94%, 84% and 11%, respectively. For the whole population, the 100-day NRM was 0% and 1-year NRM was 3%. Death was caused by transplant-associated thrombotic microangiopathy in 1 patient. For patients who were administered with Sorafenib, the 1-y NRM was 5%. Death was caused by transplant associated transplant-associated thrombotic microangiopathy. DiscussionThis retrospective study suggests that sorafenib maintenance seem to be effective even in patients pre-treated with midostaurin.